Pilgrimage, Memory, and Identity at Majeluk Heroes Cemetery, Mataram - Akbar, Muhammad Ali; Hafsah; Isnaini (Universitas prof. Dr. Moestopo (Beragama), 2026)
The tradition of visiting heroes’ graves in Majeluk Heroes Cemetery, Mataram, is a cultural practice that integrates ritual and historical commemoration. However, previous studies have largely emphasized its spiritual and social aspects, with limited analysis of its role in shaping collective memory and cultural identity in urban contexts. This study aims to examine how pilgrimage practices contribute to memory formation, cultural education, and identity construction. A qualitative field approach was employed through in-depth interviews with seven informants, participant observation, and documentation, analyzed using data reduction, categorization, and interpretative analysis. The findings show that rituals such as grave cleaning, flower scattering, and collective prayers, particularly during national and religious events, function as structured practices that reproduce historical narratives. These activities also facilitate the transmission of moral values and strengthen intergenerational engagement, especially through student participation. Analytically, the cemetery functions as a cultural space where memory, education, and identity are continuously constructed through social practice. This study demonstrates that local pilgrimage traditions operate as integrated mechanisms of memory reproduction, cultural learning, and identity formation in urban society.